The art of knitting stitches, colors, fashion - St. Clair Vision (Firm); TriCoast Studios (Princeton, NJ : Princeton Corporate Center, 2004)
Whether you're a beginner or an advanced knitter, this clear visual program demonstrates the intricacies of knitting in an effective manner and presents the history, the basics, the experts, the fun and the creativity that make knitting a popular craft.
Keywords: Instructional videos; Knitting